The effects of hesperetin on apoptosis induction and inhibition of cell proliferation in the prostate cancer PC3 cells - Shirzad Moein; Beshkar Pezhman; Heidarian Esfandiar (Shahrekord University of Medical Sciences, 2015)
ntroduction: Prostate cancer is the second leading cause of cancer-related deaths and the mostcommon cancer diagnosed in men in the United States and Europe. Hesperetin, a member of thef lavonoids with antioxidant property, is found in fruits such as oranges and red fruits. This study was undertaken to evaluate the effects of hesperetin on apoptosis induction and inhibition of cell proliferation in the prostate cancer PC3 cells.Methods: PC3 cell line was cultured in standard condition. The cells were exposed to differentconcentrations of hesperetin (0-1000 μM) for 48 hours. Cell viability was measured by MTT assay.Apoptosis induction was assessed by Annexin V-FITC by flow cytometry analysis.Results: The PC3 cells exposed to hesperetin (0-1000 μM) exhibited an IC (inhibitoryconcentration of 50%) about 450 μM. At different concentrations of hesperetin (400, 450 and 500µm), the apoptosis increased slightly (not significant) in treated PC3 cells compared to the controlgroup (5.4%, 7.8% and 9.1% respectively vs. 4.2%).Conclusion: These results clearly show that hesperetin can lead to inhibition of PC3 cellsproliferation.